Prof. Shaf Keshavjee: innovating lung transplantation and facing the challenges of the unknown - Dong, Wenbin (Journal of Thoracic Disease, 2018)
As two of the deadliest malignancies worldwide, lung cancer and esophageal cancer remain a global concern for patients and thoracic surgeons alike. The 2018 AATS meeting, Focus on Thoracic Surgery: Lung and Esophageal Cancer, concentrated on the complex issues involved with treating both lung and esophageal malignancies, while also discussing innovative approaches for improving quality and outcomes.